Programa educativo de emprendimiento social para mejorar capacidades emprendedoras en directivos y docentes de la Institución Educativa primaria de menores N° 60747 Divino Maestro Iquitos 2022 - Aguilar Tang, Adriana Magali (2024)
The present research addressed the fundamental question: What is the effect of applying an educational program focused on social entrepreneurship on the development of entrepreneurial skills in the managers and teachers of the Primary Educational Institution N°60747 Divino Maestro in Iquitos during the year 2022? The purpose of this study was to evaluate the effect derived from the application of said program in strengthening entrepreneurial skills among the aforementioned personnel. An evaluative methodological approach was adopted, characterized by a univariate, field and cross-sectional design. The population of interest was made up of 37 individuals, including both managers and teachers, who constituted the study sample. For data collection, a questionnaire, previously validated by experts in the field, was used as a measurement instrument. The results obtained after the application of the social entrepreneurship educational program revealed a substantial improvement in the entrepreneurial skills of the participants. Initially, no member of the sample had reached a level of entrepreneurial competence considered sufficient; However, after the intervention, 51.4% achieved this standard, indicating notable progress. Furthermore, the total elimination of previously identified deficiencies in these capacities was observed, underlining the effectiveness of the program to enrich the entrepreneurial profile of educational personnel.